1979
DOI: 10.1085/jgp.73.3.327
|View full text |Cite
|
Sign up to set email alerts
|

Calcium content and net fluxes in squid giant axons.

Abstract: Axons freshly dissected from living specimens of the tropical squid Dorytheutis plei have a calcium content of 68 tzmol/kg of axoplasm. Fibers stimulated at 100 impuises/s in 100 mM Ca seawater increase their Ca content by 150/zmol/ kg.min; axons placed in 3 Ca (choline) seawater increase their Ca content by 12 /zmol/kg.min. Axons loaded with 0.2-1.5 mmol Ca/kg of axoplasm extruded Ca with a half time of 15-30 min when allowed to recover in 3 Ca (Na) seawater. The half time for recovery of loaded axons poisone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

1979
1979
1986
1986

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…+ . These findings agree qualitatively first with flux measurements showing that Ca efflux is virtually fully activated by a Na 0 of 180 mM (Blaustein, 1977) and that Ca influx is virtually unaltered at this value for Na 0 (Baker et al 1969) and, second, with analytical Ca measurements (Requena et al 1979). In Table 5 below, flux values from analytical measurement of Cai and aequorin glow data are compared for several experimental variables known to alter intracellular Ca regulation.…”
Section: (D) the Effect Of External Monovalent Cations On Ca\ +supporting
confidence: 79%
“…+ . These findings agree qualitatively first with flux measurements showing that Ca efflux is virtually fully activated by a Na 0 of 180 mM (Blaustein, 1977) and that Ca influx is virtually unaltered at this value for Na 0 (Baker et al 1969) and, second, with analytical Ca measurements (Requena et al 1979). In Table 5 below, flux values from analytical measurement of Cai and aequorin glow data are compared for several experimental variables known to alter intracellular Ca regulation.…”
Section: (D) the Effect Of External Monovalent Cations On Ca\ +supporting
confidence: 79%
“…It has been suggested that the transmembrane Na and Ca gradients are electrochemically coupled so that the downhill movement of Na ions provides sufficient energy for the uphill movement of Ca. This hypothesis is supported by the recent work of Requena, Mullins & Brinley (1979). In the absence of ATP, net extrusion of Ca from previously loaded squid axons can occur only in the presence of an electrochemical gradient for Na.…”
Section: Introductionsupporting
confidence: 58%
“…This small apparent alkalinization, occurring together with the increase in resting Ca, is to be compared to observations in the absence of alcohols where a large Ca entry acidifies axoplasm (see Mullins et al, 1983 for related references and discussion). The Ca release is a negligible fraction of the total analytical Ca (68 gmol/kg axoplasm) (Requena et al, 1979). It is also known that in fresh axons (those not exposed to high Ca sea water) the mitochondria have a negligible fraction of the total analytical Ca stored (Brinley et al, 1977) so that it has usually been assumed that it is the smooth endoplasmic reticulum of the axon that stores the bulk of the Ca.…”
Section: Discussionmentioning
confidence: 99%